Reproduction of printed microtextures on Ti-Implants (Transactions on Additive Manufacturing Meets Medicine, 2024)
In order to understand and optimize the topological possibilities of the production equipment and the process, this work presents a convenient and reproducible way to analyze the capabilities to incorporate a micro texture to the printed part.
Keywords: 3D printing; metal printing; Titanium; 3D printed Implant; Scaffold; lattice structures; Metrological characterization; implant testing